Review of an Improved Longwall Panel Layout for Ground Control in Longwall Mining - Z. M. Cui; P. F. Wang; Z. Li; Y. Yang (Shock and Vibration)
Conventional longwall layout (CLL) for mining coal, trona, etc. is still fraught with problems including low resource recovery, wavy ground surface subsidence, bumps or rockbursts, gateroad support and maintenance, poisonous air hazard, spontaneous combustion in coal mines, instability of equipment at inclined, or steeply inclined working face, etc. In order to improve longwall mining, a novel alternate longwall panel layout that has been employed for over 20 years in China, Australia, and Russia, etc. is proposed termed “split-level longwall layout” (SLL). Gateroads on either end of the same SLL panel are split level, i.e., placed in different levels. This paper provides a review of existing research literature and insights on the problems encountered in CLL and the improvement of the new approach. Theoretical, numerical analysis, and field observation results of the new strategy demonstrate that the problems mentioned above in CLL are mitigated, and the development entries using the improved longwall system have a better stress environment with associated reduction in large roadway convergence, coal bumps or outbursts, and many other issues on ground control. Based on the current development of SLL and the future requirement of mining industry, the prospects as well as its applications, limitations, and concerns for SLL are presented.